APLIKASI ABSENSI JEMAAT BERBASIS ANDROID PADA GEREJA KRISTEN INDONESIA GADING SERPONG - Michael; Edy (Universitas Islam Balitar, 2022)
Abstract : It will be difficult for the congregation to attend services without having to carry a church card at all times. In order to tackle congregational issues with attendance, this research was done in order to design and develop an Android-based church attendance application. This system was designed and developed using the RAD (Rapid Application Development) methodology. The author created the program